A NON-DESCRIPT DOE'S JOURNEY TO RECOVERY FROM TOTAL UTERINE PROLAPSE SUBSEQUENT TO ABORTION - Mathew Raja; Jackson, A; Louis, S (International Journal of Allied Sciences (IJAS), 2022)
This article reports on the successful management of total uterine prolapse in a non-descript doe following an abortion. Uterine prolapse is a common occurrence in goats after parturition due to a lack of uterine tone, a dilated cervix, and/or retention of placenta. In this particular case, straining during an abortion caused the prolapse. The article details the case history and treatment procedure, which included administering epidural anesthesia, washing the prolapsed uterus, removing adhered fetal membranes, and closing the tear with a simple interrupted suture. The article recommends elevating the hindquarters of the animal for easy replacement of the prolapsed mass, and administering oxytocin and other medications to increase uterine tone. The success of the treatment depends on a systematic approach, and it is recommended that farmers receive preliminary education to prevent complications. Proper treatment involves washing and removal of adhered tissues, closure of any tears, and replacement of the prolapsed mass. Antibiotics, anti-inflammatories, and antihistamines should be administered to prevent infection and inflammation, and retention sutures and tetanus toxoid should be used for prophylaxis. Through implementing proper management techniques, uterine prolapse can be successfully treated in goats.